Basketball terminology: unification challenges - Peulic, J.; Yadreev, V. V.; Semenov, S. V. (Theory and Practice of Physical Culture, 2019)
Background. Success in the modern basketball game is known to depend on the teamwork quality secured by perfect understanding and cooperation of the players and coaches [9] - that need to be put on a sound verbal communication basis with certain standardization of phrases and signals, particularly when the teams and coaches are bi- or multilingual that is not unusual for the elite sports nowadays [2]. Prior to 1980ies the national basketball leagues were dominated by the locals speaking their mother languages. Since then the national teams have opened up to increasingly encourage inflows of foreign contractors in the competitive performance improvement efforts - and this was the reason for the growing influence of a few nations and clubs of origin of such players and experts on the national turfs on the one hand and on the basketball game popularity the world over on the other hand. Since 1990ies virtually no one elite club and nation could progress in isolation from the flows of foreign players and coaches.